The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1758-5996-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in bus and truck drivers in Kashan, Iran

Abstract: BackgroundBus and truck drivers are apparently more involved in metabolic syndrome and its complications due to their working conditions. The related impacts are not only harmful for driver's health, but also may endanger others. The present research was carried out to determine the prevalence of metabolic syndrome among bus and truck drivers in Kashan, a city in Iran.MaterialsIn 2007, 429 bus and truck male drivers were enrolled to this cross sectional study to examine the metabolic syndrome using ATPIII crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
60
5
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 21 publications
11
60
5
3
Order By: Relevance
“…This positive correlation in most cases had a significant difference (P < 0.01). These results are consistent with other studies (14,15). The majority of drivers are overweight according to BMI.…”
Section: Discussionsupporting
confidence: 83%
“…This positive correlation in most cases had a significant difference (P < 0.01). These results are consistent with other studies (14,15). The majority of drivers are overweight according to BMI.…”
Section: Discussionsupporting
confidence: 83%
“…9 In a study conducted by Saberi and others in Iran in 2011, 41% were with overweight and 23% were found to be with obesity. 10 In a study conducted by Mohebbi and others in Iranian professional drivers in 2012, overweight was found to be 41.4% cases and obesity was found to be 21.3%. 11 In the present study among the respondents those with overweight was found to be 41.1% and those with obesity was found to be 14.5% which were similar to the above studies.…”
Section: Discussionmentioning
confidence: 96%
“…The findings illustrate that for the drivers, life on the road has many effects, especially, healthrelated issues. Other researchers have also mentioned physical (11,12,23) and mental problems (9) as some of the hardships that can be caused for Iranian truck drivers during their life on the roads. Further, the present study also showed inappropriate work status, time limits and work pressure at work, as the other difficulties in the individual life of truck drivers, and this is in line with previous study, which found these issues as occupational stressors of life truck drivers (4).…”
Section: Discussionmentioning
confidence: 99%
“…They usually experience conditions which can place them in risk of encountering problems in their lives, such as going on long trips, the absence of proper resting places and unsuitable facilities on the existing road (8)(9)(10). Moreover, working and living in low mobility status, night driving or non-stop and tiring driving, and a high calorie intake predispose truck drivers to metabolic syndromes and cardiovascular problems (11). The wear and tear of vehicles, poor condition of the roads and an increase in daily work hours are some of the factors related to working living environment makes the Iranian truck drivers encounter physical (12) and mental (9) health problems.…”
Section: Introductionmentioning
confidence: 99%